Markedly different clustering of CVD risk factors in New Zealand Indian and European people but similar risk scores (PREDICT‐14) - Lavinia Perumal; Susan Wells; Shanthi Ameratunga; Romana D. Pylypchuk; C. Raina Elley; Tania Riddell; Andrew Kerr; Sue Crengle; Dudley Gentles; Rod Jackson (Elsevier, 2012)
Abstract Objective: To compare the cardiovascular disease (CVD) risk profiles of Indian and European patients from routine primary care assessments in the northern region of New Zealand. Method: Anonymous CVD risk profiles were extracted from PREDICT (a web‐based decision support program) for Indian and European patients aged 35-74 years. Linear regression models were used to obtain mean differences adjusted for age, gender and deprivation. Results: At recruitment, Indian participants (n=8,830) were younger than Europeans (n=47,091), in keeping with national guidelines that recommend earlier CVD risk assessment for Indians. Compared with Europeans, a greater proportion of Indian participants lived in areas of higher deprivation and had a two to four‐fold greater burden of diabetes in all age groups. Indian participants had a significantly lower proportion of smokers and a lower mean systolic blood pressure. The respective cardiovascular risk factor profiles lead to similar age‐adjusted Framingham five‐year CVD risk scores. Conclusions and implications: National data sources indicate that there are higher rates of hospitalisations and deaths from CVD in Indians compared with Europeans. Our study found similar predicted CVD risk in these two populations despite markedly different clustering of risk factors, suggesting that the Framingham risk equation may underestimate risk in Indians. There is a need for better ethnicity coding to identify all South Asian ethnicities.